ETHNOMATHEMATICS IN PRACTICE: MATHEMATICAL CONCEPTS IN PANDEGLANG'S TRADITIONAL BALOK CAKE - Nenden Suciyati Sartika; Peni Permatasari; Eka Rosdianwinata (PT. ZILLZELL MEDIA PRIMA, 2025)
The purpose of this study is to determine the relevance of Pandeglang's traditional food, Kue Balok, to mathematics learning using the Ethnomathematics approach. Ethnomathematics is one of the applications of mathematics learning related to culture. This research was conducted at Kue Balok Babakan Hj. Djamsinah located in Montor, Pagelaran District, Pandeglang Regency, Banten. The object of ethnomathematics study in this study is Pandeglang's traditional food, Kue Balok. The type of research used is exploratory research with an ethnographic approach. Data collection methods used are observation, interviews, and documentation. The results of the study indicate that mathematics learning using the traditional Pandeglang food, kue blok, as an object can be linked to geometry and flat-sided solids. The shape of the kue blok itself represents the concept of a cuboid, so it can be used to introduce concepts such as volume and surface area. Its relevance to mathematics learning lies in its potential as a contextual learning medium that can bridge students' understanding of abstract mathematical concepts. Thus, ethnomathematics in kue blok can be used to create mathematics learning that is more meaningful and relevant to students' local culture.